A case of asymptomatic ileal duplication cyst associated with acute appendicitis - Hülya İpek; Gül Doğan; Dilek Yılmaz; Mehmet Metin; Çağatay E. Afşarlar (Elsevier, 2017)
Duplications of the alimentary tract are infrequent anomalies. They are most frequently located in the terminal ileum, and majority of them became symptomatic before the age of 2. Presenting symptoms may include abdominal mass, intestinal obstruction, intussusception, rectal bleeding, and abdominal pain. Preoperative diagnosis is usually difficult, intra-abdominal duplications are usually diagnosed during surgical explorations of above complications. We presented a 12-year-old girl with asymptomatic ileal duplication cyst associated with non-complicated acute appendicitis, whose imaging studies at admission were compatible with complicated perforated appendicitis.